Cultural literacy building of primary school students as basic concept - Ma'as Sobirin; Peni Susapti (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2018)
The low literacy ability of the society will have an impact on the quality of human resources. Nowadays, literacy (read-write) has not yet become a necessity of life and part of nation's culture. Schools as the primary means of shaping the character of students need to plan programs that lead to literacy culture as a solution to the problem. Currently, schools are busy implementing government programs through literacy programs with the aim of the growing awareness of students in familiarizing the culture. This program provides the significant influence for students with various forms of activities undertaken by school. On this occasion, the writer tries to present some explanations related to the basic concepts, urgency, stapes of cultural development of literacy and the form of programs that can be done in supporting of literacy culture in Elementary School.